How Does PNPM-MP Impact the Income of Poor People? (Case Study of SPP Members in Sumanik Village, Tanah Datar Regency) - Lusi Sesmita; Nur Ari Sufiawan; Bintang Rizky AMS; Weriantoni Weriantoni (Universitas Bangka Belitung, 2025)
In Nagari Sumanik, Salimpaung District, and Tanah Datar Regency, poverty issues require coordinated and collaborative actions from all parties. The local government launched the National Program for Rural Independent Community Empowerment (PNPM-MP) to improve poverty alleviation and job creation. PNPM-MP is a poverty alleviation effort that involves community members to improve the quality of life, independence, and welfare. The objectives of this study were to determine the differences in production before and after receiving SPP funds from PNPM-MP, the differences in employment opportunities before and after receiving SPP funds from PNPM-MP, and the differences in income before and after receiving SPP funds from PNPM-MP. This research found that there were significant differences in production, employment opportunities and income before and after receiving SPP funds from PNPM. Similarly, the Wilcoxon Signed Rank Test for income showed an asymp. Sig (2-tailed) value of 0.000 < 0.05, confirming a significant difference before and after receiving SPP funds.